Investigating the Sensitivity Effect of Actuarial Assumptions on Pension Liabilities in Malaysia (Baghdad Science Journal, 2021)
Malaysia will be an ageing population by 2030 as the number of those aged 60 years and above has increased drastically from 6.2 percent in 2000 and is expected to reach 13.6 percent by 2030. There are many challenges that will be faced due to the ageing population, one of which is the increasing cost of pensions in the future. In view of that, it is necessary to investigate the effect of actuarial assumptions on pension liabilities under the perspective of ageing. To estimate the pension liabilities, the Projected Unit Credit method is used in the study and commutation functions are employed in the process. Demographic risk and salary risk have been identified as major risks in analyzing pension liabilities in this study. The sensitivity analyses will be conducted in the study to investigate how the pension liabilities will be affected when these major risks changes. This study analyzes nine scenarios under assumptions in the actuarial model, namely age of retirement, rate of mortality and rate of salary growth. The result of this study indicates that the implied mortality experience and salary growth rate assumptions have a significant impact on pension liabilities.